Einstein-Riemann gravity on deformed spaces - Wess, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
A differential calculus, differential geometry and the E-R Gravity theory are studied on noncommutative spaces. Noncommutativity is formulated in the star product formalism. The basis for the gravity theory is the infinitesimal algebra of diffeomorphisms. Considering the corresponding Hopf algebra we find that the deformed gravity is based on a deformation of the Hopf algebra.